Evaluation of simplified methods of analysis of yielding structures with damping systems - Ramirez, Oscar M.; Constantinou, Michael C.; Gomez, Juan D.; Whittaker, Andrew S.; Chrysostomou, Christis (My University, 2002)
The 2000 NEHRP Provisions include simplified methods of analysis of inelastic buildings equipped with linear viscous, nonlinear viscous, and hysteretic damping devices. These methods are based in part on the data presented in the paper. Nonlinear response-history analysis was used to validate the methods. The derivation of the 2000 NEHRP simplified methods for calculating the maximum acceleration and maximum velocity in damped framing systems are presented. These simplified methods produce exact or conservative estimates of peak displacement and peak acceleration, and reasonable estimates of peak velocities. The estimated velocities are within 25% of the average values obtained from response-history analysis for a broad range of periods and damping ratios. Velocity correction factors are provided to calculate peak velocity given the pseudo-velocity.
Keywords: Structural design--Abstracts--Periodicals; Damping (Mechanics); Hysteresis.